Mobile Legends dan Dampak Toksik: Refleksi Sikap dan Perilaku Remaja dalam Perspektif Pendidikan Agama Islam - Qhomariah, Esti Nurul; Fuad, Ai Fatimah Nur; Darraz, Muhammad Abdullah; Wibowo, Heru (IAI Nasional Laa Roiba Bogor, 2024)
Mobile Legends, as an online game that is popular among teenagers, has attracted the attention of many parties regarding the social and behavioral impacts that may arise from interactions in the game. This scientific article aims to explore the toxic impact of Mobile Legends on adolescent attitudes and behavior, with a focus on the perspective of Islamic religious education. This study uses a qualitative approach in the form of interviews to collect data from teenagers who actively play Mobile Legends. Through in-depth interviews, this research tries to identify patterns of toxic behavior in games and analyze how the values of Islamic religious education can shape teenagers' understanding of the concepts of justice, tolerance and ethics in the context of online games. The research results show that there is a correlation between the intensity of playing Mobile Legends and changes in teenagers' attitudes and behavior. Apart from that, this article also discusses Islamic education strategies that can be implemented to overcome toxic impacts that may arise, including the formation of moral character, instilling Islamic values, and promoting mutual respect in cyberspace. It is hoped that this article will provide deeper insight into the relationship between Mobile Legends and its toxic impact on adolescent attitudes and behavior, as well as contribute to the development of Islamic religious education in facing modern challenges such as online games which can influence the mindset and behavior of the younger generation.